Access to Nutrition Information, Dietary Diversity and Shortfall Food Groups among Nigerian In-School Adolescents - Ariyo O; Oladipo FS; Alimi EJ; Atojoko MA (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2023)
Background: Healthy dietary behaviour is essential for adolescents to promote psychosocial development and cognitive performance and prevent nutrition-related chronic diseases. Yet, the prevalence of micronutrient malnutrition remains high among Nigerian adolescents. Objective: To assess access to nutrition information, dietary diversity, and shortfall food groups among in-school adolescents in Mokola, Ibadan, Oyo, Nigeria. Methods: This descriptive, cross-sectional study involved 360 in-school adolescents selected using a multistage sampling technique. The data, which included sociodemographic characteristics, access to nutrition information and dietary intake, were obtained using a semi-structured, interviewer-administered questionnaire. Dietary intake was assessed using a 24-hour recall approach to determining dietary diversity using Food and Agriculture Organisation (FAO)'s Minimum Dietary Diversity for Women procedure. Results: The mean age of the respondents was 15.5±2.3 years, and 58.1% were females. Only 5.4% had access to information on healthy eating. The minimum dietary diversity score during the previous 24 hours was 5.41±1.3, and only 46.5% of the respondents met the minimum dietary diversity for women. Shortfall food groups included nuts and seeds (4.1%), dairy foods (6.1%), pulses (7.2%), fruits (10.3%), other vegetables (10.3%), and eggs (15.3%). Conclusion: Poor access to nutrition information and low dietary diversity were observed among in-school adolescents in Mokola, Ibadan, Nigeria. Policymakers should strengthen the educational system to promote active learning of healthy eating and improve access to the varieties of foods and snacks made from the shortfall food groups.